COMPARISON BETWEEN OPEN SURGERY AND ENDOVASCULAR REPAIR IN THE TREATMENT OF ABDOMINAL AORTIC ANEURYSM: AN INTEGRATIVE REVIEW (CIPEEX, 2025)
Introduction: Abdominal aortic aneurysm (AAA) is a serious vascular condition that predominantly affects elderly individuals and those with cardiovascular risk factors, representing an important cause of morbidity and mortality worldwide. Two main surgical techniques are used: open repair (OAR) and endovascular repair (EVAR). Although both are widely performed, their selection remains controversial regarding perioperative mortality, long-term survival, complications, quality of life, and reinterventions. Objective: To compare clinical outcomes between OAR and EVAR based on recent scientific evidence. Methods: An integrative review was conducted through searches in PubMed Central and the Virtual Health Library (VHL). Inclusion criteria were original studies published between 2019 and 2024, with free full-text access, directly comparing OAR and EVAR in patients with AAA. Systematic reviews, non-comparative studies, and articles without clear clinical outcomes were excluded. Five studies met the criteria and were analyzed. Results: The findings indicated that EVAR is associated with lower perioperative mortality, shorter operative time, reduced blood loss, and shorter hospital stay, which makes it an attractive option for patients at high surgical risk, especially the elderly. However, EVAR demonstrated a higher incidence of late aneurysm-related complications and an increased need for reinterventions in long-term follow-up. In contrast, OAR was linked to higher immediate morbidity and longer hospital stay, but lower reintervention rates and, in some cohorts, greater five-year survival. Quality of life assessments revealed that patients undergoing EVAR reported faster recovery and higher satisfaction in the early postoperative months, although differences between the two groups diminished over time. Mortality at five years was generally comparable, though some studies suggested greater long-term durability with OAR in selected populations. Conclusion: Both techniques present specific advantages, and the choice should be individualized according to patient age, comorbidities, anatomical conditions, and surgical risk. EVAR may be preferable for high-risk candidates due to its immediate safety profile, while OAR may represent a more durable approach for clinically fit patients. The therapeutic decision must be multidisciplinary and evidence based. Future prospective studies with follow-up beyond ten years are needed to clarify long-term outcomes and improve patient selection.
Keywords: Abdominal aortic aneurysm; Endovascular procedures; Open surgical repair; Reintervention